Pengaruh Suplementasi Rumput Laut Eucheuma cottonii terhadap Kadar VFA dan NH3 Cairan Rumen Sapi Potong - Afrianti, Zulvina; Muhtarudin, Muhtarudin; Liman, Liman; Erwanto, Erwanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2025)
This study aims to determine the supplementation of seaweed (Eucheuma cottonii) against levels of Volatile Fatty Acid (VFA) and ammonia (NH3) of beef cattle rumen fluid. This research will be carried out in October – December 2023 at the Maju Sejahtera Livestock Production Cooperative, Damai Jaya Village, Tanjung Sari District, South Lampung Regency. This study was conducted using Randomized Group Design consisting of 3 treatments and 6 repeats, using 18 local beef cattle. The treatment given is P1; pakchong grass + concentrate (ratio 70% : 30% BK feed), P2; pakchong grass + concentrate (ratio 70% : 30% BK feed) + seaweed Eucheuma cottonii (4% BK feed) and P3; pakchong grass + concentrate (ratio 70% : 30% BK feed) + seaweed Eucheuma cottonii (4% BK feed) + biochar (0.05% BK feed). Variables observed include levels of Volatile Fatty Acid (VFA) and Ammonia (NH3) of beef cattle rumen fluid. The data obtained were analyzed using Analysis of Variance at the level of 5%. The results of this study showed that seaweed supplementation (Eucheuma cottonii) was not significantly different (P>0.05) from Volatile Fatty Acid (VFA) levels and ammonia (NH3) levels. P3 treatment can potentially increase Volatile Fatty Acid (VFA) and Ammonia (NH3) levels in beef cattle rumen fluid.